2017
DOI: 10.1021/acs.jafc.7b03316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interaction between Cadmium (Cd) and Selenium (Se) on Grain Yield and Cd and Se Accumulation in a Hybrid Rice (Oryza sativa) System

Abstract: A pot experiment was conducted to investigate the interactive effects of cadmium (Cd) and selenium (Se) on their accumulation in three rice cultivars, which remains unclear. The results showed that Se reduced Cd-induced growth inhibition, and increased and decreased Se and Cd concentrations in brown rice, respectively. Cadmium concentrations in all tissues of the hybrid were similar to those in its male parent yet significantly lower than those in its female parent. Selenium reduced Cd accumulation in rice whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…2), indicating Se application can inhibit Cd absorption in winter wheat. Huang et al [20] found that Se application reduced Cd concentration in brown rice by doing a pot experiment, and Lin et al [21] reported that Se decreases the toxicity and accumulation of Cd in rice by reducing Cd uptake. Plants absorb nutrients mainly through the root system [22].…”
Section: Discussionmentioning
confidence: 99%
“…2), indicating Se application can inhibit Cd absorption in winter wheat. Huang et al [20] found that Se application reduced Cd concentration in brown rice by doing a pot experiment, and Lin et al [21] reported that Se decreases the toxicity and accumulation of Cd in rice by reducing Cd uptake. Plants absorb nutrients mainly through the root system [22].…”
Section: Discussionmentioning
confidence: 99%
“…1), indicating Se supply could inhibit Cd absorption in winter wheat. Huang et al [21] found that Se application reduced Cd concentration in brown rice via a pot experiment, and Lin et al [22] reported that Se decreasing the toxicity and accumulation of Cd in rice was related to the reduced Cd uptake. Plants absorb nutrients mainly through the root system [23].…”
Section: Discussionmentioning
confidence: 99%
“…Cd causes DNA damage in rice. Cd 2+ can cause abnormal DNA methylation, which affects gene viability, interferes with the synthesis of enzymes and proteins, and fundamentally causes damage to crop growth and development [35]. Low concentration of Cd 2+ promoted the respiration rate of rice leaves.…”
Section: Discussionmentioning
confidence: 99%